(untitled) (Società e diritti, 2022)
Abstract The paper deals with the main problematic profiles of sports justice, both the internal ones and those arising from the possible relations between the sports regulation and the state system, in the perspective of a role that is neither exclusively ancillary nor merely receptive of sports justice with respect to jurisdiction; the relationship between which must instead be characterized by dialogue and a logic of reciprocity, capable of implementing, without prejudice to its primacy, even jurisdiction itself.